2015
DOI: 10.1080/14786419.2015.1016938
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin-producing endophytic fungus isolated from a medicinal plant Solanum xanthocarpum

Abstract: Lovastatin is a potent drug for lowering blood cholesterol. An endophytic fungus Phomopsis vexans was isolated from the healthy leaf tissues of Solanum xanthocarpum, a medicinal plant, and screened for lovastatin production. The fungus was identified by their characteristic cultural morphology and molecular analysis. The strain had a component with the same TLC Rf value and HPLC retention time as authentic lovastatin. The presence of lovastatin was further confirmed by FT-IR, UV, (1)H, (13)C NMR and LC-MS anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Polyketides exhibit a wide range of bioactivities such as antibacterial (e.g., tetracycline), antifungal (e.g., amphotericin B), anticancer (e.g., doxorubicin), antiviral (e.g., balticolid), immune-suppressing (e.g., rapamycin), anti-cholesterol (e.g., lovastatin), and anti-inflammatory activity (e.g., flavonoids) [3,4,5,6,7,8,9]. Some organisms can produce polyketides such as bacteria (e.g., tetracycline from Streptomyces aureofaciens ) [10], fungi (e.g., lovastatin from Phomopsis vexans ) [11], plants (e.g., emodin from Rheum palmatum ) [12], protists (e.g., maitotoxin-1 from Gambierdiscus australes ) [13], insects (e.g., stegobinone from Stegobium paniceum ) [14], and mollusks (e.g., elysione from Elysia viridis ) [15]. These organisms could use the polyketides they produce as protective compounds and for pheromonal communication in the case for insects.…”
Section: Introductionmentioning
confidence: 99%
“…Polyketides exhibit a wide range of bioactivities such as antibacterial (e.g., tetracycline), antifungal (e.g., amphotericin B), anticancer (e.g., doxorubicin), antiviral (e.g., balticolid), immune-suppressing (e.g., rapamycin), anti-cholesterol (e.g., lovastatin), and anti-inflammatory activity (e.g., flavonoids) [3,4,5,6,7,8,9]. Some organisms can produce polyketides such as bacteria (e.g., tetracycline from Streptomyces aureofaciens ) [10], fungi (e.g., lovastatin from Phomopsis vexans ) [11], plants (e.g., emodin from Rheum palmatum ) [12], protists (e.g., maitotoxin-1 from Gambierdiscus australes ) [13], insects (e.g., stegobinone from Stegobium paniceum ) [14], and mollusks (e.g., elysione from Elysia viridis ) [15]. These organisms could use the polyketides they produce as protective compounds and for pheromonal communication in the case for insects.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have screened several microbes for the production of lovastatin, a secondary metabolite, from various niches [26]. Although, there are many endophytic fungi that are being exploited for various pharmaceutically valuable secondary metabolites, there are a very few reports of lovastatin being produced by endophytic fungi [19,22]. A study demonstrated that the endophytic fungi are poor producers of lovastatin since none of the 54 endophytic fungi isolated by us from medicinal plants produced lovastatin even after prolonged growth period [20].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they are exploited to grow as axenic cultures on synthetic media under controlled conditions (devoid of interaction with host plant) for the production of commercially valuable secondary metabolites with anticancer, antioxidant, anti-inflammatory, antiparasitic, antiviral, and antimicrobial properties. However, there are very few reports on the production of lovastatin by endophytic fungi [19,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In bacteria, the actinomycetes (streptomycetes) produce a significant number of chemically distinct secondary metabolites [73][74][75][76]. Other major sources include soil pseudomonas, bacilli, and myxococci [77][78][79][80]. An example of a bacterial secondary metabolite is botulinum toxin synthesized by Clostridium botulinum, with a positive and negative effect on humans.…”
Section: Bacterial Secondary Metabolitesmentioning
confidence: 99%